2020
DOI: 10.3390/ijerph17103355
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Antimicrobial Susceptibility Reduction amongst HIV-Infected Individuals at the University Teaching Hospital, Lusaka, Zambia

Abstract: Increased antimicrobial resistance among Human Immunodeficiency Virus (HIV)-infected individuals to commonly used antibiotics in the treatment of gastroenteritis is a public health concern, especially in resource-limited settings. We set out to compare the antimicrobial susceptibility pattern of Escherichia coli (E. coli) isolates from HIV-infected and HIV-uninfected individuals at a tertiary hospital in Lusaka, Zambia. An analytical cross-sectional study was conducted at the University Teaching Hospital from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
2
1
2
Order By: Relevance
“…Additionally, contrary to previous studies ( Kaonga et al, 2017 ; Chabala et al, 2020 ), we found a male preponderance in this study (61.5%) probably due to the gender disparity that has been reported that women are less likely to participate in science and medicine ( Gayet-Ageron et al, 2019 ). In our study, at least two-thirds of HCPs believed individual variations can lead to different individual experiences with given medicines, similar to other studies ( Mahmutovic et al, 2018 ), which is important in the implementation of any PGx clinical care ( Muzoriana et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, contrary to previous studies ( Kaonga et al, 2017 ; Chabala et al, 2020 ), we found a male preponderance in this study (61.5%) probably due to the gender disparity that has been reported that women are less likely to participate in science and medicine ( Gayet-Ageron et al, 2019 ). In our study, at least two-thirds of HCPs believed individual variations can lead to different individual experiences with given medicines, similar to other studies ( Mahmutovic et al, 2018 ), which is important in the implementation of any PGx clinical care ( Muzoriana et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We followed patients with preserved kidney function and no known history of diabetes or underlying comorbidities that were initiating TDF-based ART from December 2018 to November 2019 for approximately three months from the day they initiated therapy. Consistent with other studies [41,42], we found a female preponderance in our study probably because females tend to be more willing to participate in studies than males. Compared to baseline, there was a 29 μmol/L increase in serum creatinine concentration observed at 3-months following therapy initiation, consistent with findings that TDF therapy leads to nephrotoxicity and reduced renal function in the first three to six months [27,43].…”
Section: Discussionsupporting
confidence: 93%
“…; DeWitt et al, 2019;Chabala et al, 2020), in this study the prevalence was low in patients that presented with diarrhoea. The observed low prevalence in patients that presented with diarrhoea seem to support the observation ofMedina et al (2010) that prevalence of E. coli was low in patients that adhere to the highly active antiretroviral therapy (HAART).…”
supporting
confidence: 43%